Exercise Training in Obese Rats Does Not Induce Browning at Thermoneutrality and Induces a Muscle-Like Signature in Brown Adipose Tissue - Aldiss, Peter; Lewis, Jo E.; Lupini, Irene; Bloor, Ian; Chavoshinejad, Ramyar; Boocock, David J.; Miles, Amanda K.; Ebling, Francis J. P.; Budge, Helen; Symonds, Michael E. (Frontiers in Endocrinology, 2020)
Aim: Exercise training elicits diverse effects on brown (BAT) and white adipose tissue (WAT) physiology in rodents housed below their thermoneutral zone (i.e. 28-32°C). In these conditions, BAT is chronically hyperactive and, unlike human residence, closer to thermoneutrality. Therefore, we set out to determine the effects of exercise training in obese animals at 28°C (i.e. thermoneutrality) on BAT and WAT in its basal (i.e. inactive) state. Methods: Sprague-Dawley rats (n=12) were housed at thermoneutrality from 3 weeks of age and fed a high-fat diet. At 12 weeks of age half these animals were randomised to 4-weeks of swim-training (1 hour/day, 5 days per week). Following a metabolic assessment interscapular and perivascular BAT and inguinal (I)WAT were taken for analysis of thermogenic genes and the proteome. Results: Exercise attenuated weight gain but did not affect total fat mass or thermogenic gene expression. Proteomics revealed an impact of exercise training on2-oxoglutarate metabolic process, mitochondrial respiratory chain complex IV, carbon metabolism and oxidative phosphorylation. This was accompanied by an upregulation of multiple proteins involved in skeletal muscle physiology suggesting an adipocyte to myocyte switch in BAT. UCP1 mRNA was undetectable in IWAT with proteomics highlighting changes to DNA binding, the positive regulation of apoptosis, HIF-1 signalling and cytokine-cytokine receptor interaction. Conclusion: Exercise training reduced weight gain in obese animals at thermoneutrality and is accompanied by an oxidative, myogenic signature in BAT, rather than induction of thermogenic genes. This may represent a new, UCP1-independent pathway through which BAT physiology is regulated by exercise training.